Internalisasi Nilai Pendidikan Islam dalam Menumbuhkan Kesadaran Multikultural Siswa: Studi Kasus di MAN 1 Pamekasan - Abdul Halim (Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the process of internalizing Islamic education values in fostering students' multicultural awareness at MAN 1 Pamekasan. Using a qualitative case study design, data were collected through participatory observation, in-depth interviews with 13 informants (the principal, teachers, and students), and documentation studies of lesson plans, policies, and activity archives. The findings reveal that the internalization occurs effectively through integrative and reflective strategies that go beyond the formal curriculum, where teachers act as transformative murabbis (educators) who connect maqashid sharia principles with the context of diversity. The co-curricular ecosystem functions as a social laboratory for practicing values such as shura (deliberation) and ‘adl (justice). Consequently, the transformation of students' awareness progresses from passive tolerance to active roles as peacebuilding agents. This research yields a conceptual framework called the Maqashid-based Integrative Internalization Model (MIIM), which synthesizes four pillars: maqashid as a theological foundation, the integration of Islamic, national, and local wisdom values, critical-reflective learning, and structured action spaces. This model offers a contextual operational framework for madrasahs and other Islamic educational institutions to strengthen their contribution in building social cohesion within pluralistic societies.